Energy performance of demonstrated building with Insulated roof and ceiling in tropical climate / Norzita Jaafar - Jaafar, Norzita (2009)
It is a generally held view that, in tropical countries like Malaysia, insulated building is more sympathetic to the prevailing climate and provides comfortable interiors. This study analyses the benefits of roof pitch insulation and ceiling insulation in 24-hour cooling mode using field data. The Twin Energy Efficiency Test Cells with identical building design and constructions have been built in the main campus of University Technology MARA in Shah Alam, Selangor and named as Test Cell A and Test Cell B. The dimensions of both test cells are 4.0m x 4.0m x 4.5m and equipped with 950W split air conditioning system were used. The evaluation of thermal and energy performance were done by analyzing the indoor temperature, attic temperature, outdoor temperature and cooling load. In this research, all data were collected using automated data logging system for 5days roof pitch insulation and lOdays ceiling insulation in 10 minute interval. Interestingly, it was found that by installing insulation material at the roof pitch, the performance better than installed above ceiling. For roof insulation showed energy saved per day was almost 0.42kWh or 2.52%.